2014
DOI: 10.1186/s40478-014-0076-z
|View full text |Cite
|
Sign up to set email alerts
|

Reducing hippocampal extracellular matrix reverses early memory deficits in a mouse model of Alzheimer’s disease

Abstract: Alzheimer’s disease is caused by increased production or reduced clearance of amyloid-β, which results in the formation amyloid-β plaques and triggers a cascade of downstream events leading to progressive neurodegeneration. The earliest clinical symptoms of Alzheimer’s disease, i.e., memory loss, are however poorly understood from a molecular and cellular perspective. Here we used APPswe/PS1dE9 (APP/PS1) transgenic mice to study the early pre-pathological effects of increased amyloid-β levels on hippocampal sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 67 publications
6
92
2
1
Order By: Relevance
“…These increases in expression occurred with impairment of long-term potentiation and contextual memory, before the onset of plaque formation. Interestingly, chondroitinase ABC injection into the hippocampus restored both long-term potentiation and contextual memory performance [133]. Another recent study used laser capture microdissection (LCM) to excise hippocampal subareas CA1 and subiculum of 40 AD brains with subsequent LC-MS/MS-based proteomics.…”
Section: Changes In Brain Ecm In Neurodegenerative Conditionsmentioning
confidence: 99%
“…These increases in expression occurred with impairment of long-term potentiation and contextual memory, before the onset of plaque formation. Interestingly, chondroitinase ABC injection into the hippocampus restored both long-term potentiation and contextual memory performance [133]. Another recent study used laser capture microdissection (LCM) to excise hippocampal subareas CA1 and subiculum of 40 AD brains with subsequent LC-MS/MS-based proteomics.…”
Section: Changes In Brain Ecm In Neurodegenerative Conditionsmentioning
confidence: 99%
“…ADAMTS family members may be utilized to develop therapies for neurodegenerative and neurological disorders. Recently, Veǵh and collaborators [84] reported that increased ECM proteins, including brevican, hyaluronan and proteoglycan link protein 1, neurocan and tenascin-R, were found at an early age in Alzheimer model mice associated with a loss of contextual fear memory and long-term potentiation (LTP) defect. The behavioral plasticity (fear conditioning) and physiological plasticity (LTP) are early affected in APP/PS1 mice and that treatment with chondroitinase ABC reverses these early deficits.…”
Section: The Possible Functions Of Adamts Proteases In Admentioning
confidence: 99%
“…Genetic alterations or environmental stimuli that affect the composition of the ECM are thought to contribute to neurodegenerative and psychiatric disorders, including drug addiction (Lubbers et al, 2014a;Vegh et al, 2014). The ECM consists mainly of deposits of hyaluronic acid, glycoproteins and proteoglycans in the extracellular space (Dityatev and Schachner, 2003).…”
Section: Introductionmentioning
confidence: 99%